KEBIJAKAN PERTANGGUNGJAWABAN PIDANA NOTARIS SEHUBUNGAN DENGAN KEDUDUKANNYA SEBAGAI PEJABAT PEMBUAT AKTA - Edi Purnomo, Eko Soponyono, Purwoto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
In UUJN doesn't regulate peculiarly hit criminal rule, only regulate rule hits stoppage and sanction towards notary public, that is in section 12, section 13, and paragraph 84 because contractual terms that between notary public with the parties stay in civil law domains, but contractual terms can be pulled in criminal law domain. Watchfulness aim skripsi this is to detect wisdom accountability notary public criminal answer in respect of with the position as deed maker official in this time and how wisdom accountability notary public criminal answer in respect of with the position as deed maker official. Method approaches that used in this watchfulness is juridical normatif, law ingredient and data is got to pass field study and literature study. secondary data that is got to pass book study. Based on analysis descriptive watchfulness is known case withdrawal in criminal law domain happens when found infringement belonging of one of the parties and side that harmed to report case to investigator that from botary deed investigator that is from botary deed impact crime that done by notary public, good in the position as have a share also help one of the parties so that harm other party, thereby notary public function that entrusted by uujn section 16 verse (1) font a must neutral and must not side with breached. criminal law rule related to infringement that done notary public, related to authentic deed in kuhp is regulated in paragraph 263 jo 264 KUHP so that criminal rule in paragraphs at UUJN that accountability notary public answer starting from KUHP.